Information and communication technology for development (ICT4D) - Heeks, Richard (Abingdon, Ox : Routledge, 2018)
This is the first dedicated textbook to examine and explain these emerging phenomena of Information and Communication Technology for Development. It will help students, practitioners and researchers understand the place of ICTs within development; the ICT-enabled changes already underway; and the key issues and interventions that engage ICT4D practice and strategy. The book uses extensive in-text diagrams, tables and boxed examples with chapter-end discussion and assignment questions and further reading. Supported by online activities, video links and session outlines and slides, this textbook provides the basis for undergraduate, postgraduate and online learning modules on ICT4D.
1. Understanding ICT4D -- 2. Foundations of ICT4D -- 3. Implementing ICT4D -- 4. ICTS and economic growth -- 5. ICTS, poverty and livelihoods -- 6. ICTS and social development -- 7. e-Governance and development -- 8. ICTS and environmental sustainability -- 9. The future of ICT4D.
Includes bibliographical references and index.
Keywords: ECONOMIC DEVELOPMENT